MAINTAIN BALANCE BETWEEN MARINE AND TERRESTRIAL ECOSYSTEMS AND SALUTATION MOVEMENT WITHIN THE DULUPI DISTRICT TO SUPPORT THE ACHIEVEMENT OF SDGs VILLAGE CARE FOR THE ENVIRONMENT - Muhammad Kasim; Ahmad Zainuri (Univeristas Negeri Gorontalo, 2022)
The villages of Dulupi and Tabongo are located in Dulupi, Boalemo Regency, Gorontalo Province. This village is one of the Thematic Community Services Plan Villages in the Building Period II 2021. The objective of this activity is to support the village in reaching the village's SDGs. The method of activity is carried out in five stages, namely the preparation stage, the site survey stage, the reforestation movement stage, the tree planting stage and the maintenance stage. Mangrove planting was carried out in the village of Tabongo on the island of Langala by planting 200 mangrove seedlings. In Dulupi Village, 300 mahogany trees and 300 fruit trees were planted. It is expected that this activity will maintain the balance of terrestrial and marine ecosystems and reduce the risk of flooding, strong winds and waves.